Effectiveness of Rehabilitation of Kelep River Watershed in West Lombok Regency - Welmy Soumena; Taslim Sjah; I Ketut Budastra (Jurnal Biologi Tropis, 2026)
This study aims to evaluate the effectiveness of Kelep River Watershed (DAS) rehabilitation based on biophysical indicators, including changes in vegetation cover, growth success rate, and erosion dynamics. The research approach used a mixed methods with a Before After Control Impact (BACI) design. Quantitative data were analyzed using NDVI values, the USLE erosion model, and the R/C ratio, while qualitative data were obtained through interviews and focus group discussions (FGDs). The results showed an increase in vegetation cover, indicated by an increase in NDVI values of 0.12–0.25, which contributed to a 57% reduction in erosion rates in the upstream area. Increased soil organic matter content increased infiltration and supported agroforestry productivity. Economically, the R/C ratio reached 1.67, indicating the financial viability of post-rehabilitation agriculture. Watershed rehabilitation needs to be strengthened through soil and water conservation in erosion-prone zones, regular NDVI-based monitoring, the development of multi-strata agroforestry conservation agribusiness with economic incentives, and strengthening the role of local institutions through technical support, access to capital, and monitoring of IPPKH compliance.